IDENTIFICATION OF TECHNOLOGICAL DISTRICTS: THE CASE OF SPAIN - Antonio Fuster Olivares; Jose Miguel Giner Pérez; MJesús Santa María Beneyto (European Regional Science Association (ERSA), 2011)
In recent years, several contributions have been focused on a new sort of productive systems that share some characteristics with Marshallian industrial districts. These contributions have analysed the competitiveness of these new areas and how have been promoted by policy makers. In this line, the Marshallian concept of industrial district has been increasingly related to high technology and innovation in order to analysis technological districts or clusters. The aim of this research is to show how these new areas have characteristics are not similar to those shown by traditional industrial districts. Therefore, framework and techniques for analysis that have been traditionally used for industrial districts must be adapted for identifying technological districts. Specifically, some reflections about the framework analysis of sector and spatial units are introduced in the first part of this research as well as those techniques that can be useful to identify and analyse technological districts. Next, the analysis is focused on the identification of technological districts in Spain. A multivariate analysis will be applied to calculate a synthetic index that will be used to identify those areas with a high degree of specialization in high and medium technology activities. This synthetic index will collect data about those technological activities that are involved not only in manufacturing but also in activities of innovation and R&D. Until now, there have been not many attempts to identify technological clusters through the application of quantitative methodologies; therefore, the purpose of this research is to contribute to the enhancement of knowledge about these areas in Spain.
Keywords: 330; technological districts; clusters; location; spatial agglomerations